Ecological responses of arthropods to volcanism - Ruggiero, Adriana (2014)
The explosive eruption of the PuyehueCordón Caulle (PCC) volcanic complex on June 4th 2011 changed substantially the physiognomy of landscapes in northwestern Patagonia (Argentina). The ash fall resulting from this powerful eruption blanketed several million hectares, and prevailing westerly winds during and after the event generated steep ashfall gradients (Gaitán et al. 2011) (Fig. 1) with important effects on spatial heterogeneity. Several research groups conducting ongoing research projects in northern Patagonia envisaged the spatial heterogeneity generated by the ash fall as a natural experiment that offered a unique opportunity to evaluate ecological effects of these unpredictable and extreme events.